An Analysis of Health Personnel based on Workload using the WISN Method in Hospital Melati Perbaungan - Syaifullah Syaifullah; Ermi Girsang; Sri Lestari Nasution; Tan Suyono (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Problems that often occur in organizations are the lack of the number and types of personnel needed, lack of competence (knowledge, skills, attitudes and values) of nursing staff and limited funds from hospitals so that they cannot add and maintain the human resources (HR) they need. . This study aims to determine the need for health workers by calculating the ideal number of health workers (nurses and pharmacists) based on the workload at the Melati Perbaungan General Hospital. This research is a qualitative research using observation techniques, interview guidelines and document review. This study uses research informants where the informants used are the head of the nursing room and the nurse in the inpatient room. Data analysis is the process of systematically searching and compiling data obtained from the results of field observations (work sampling), in-depth interviews and document review. The results obtained: 1) The total use of time for nurses during observations is known that the use of time for direct nursing activities of implementing nurses in the inpatient room is 36.3%, indirect nursing activities is 40.6% and personal activities is 23.1 %. This shows that the activities that are mostly carried out by nurses are indirect nursing activities. This is because nursing activities do not directly have to be carried out and completed in accordance with nursing procedures.